Pengaruh video edukasi sadar gizi terhadap tingkat pengetahuan dan sikap terkait gizi pada wanita gizi lebih di wilayah perkotaan - Palupi, Khairizka Citra; Sari, Ria Patika; Gifari, Nazhif; Sitoayu, Laras (Jurnal Gizi Klinik Indonesia, 2023)
The effect of mindful nutrition educational video on knowledge levels and attitudes related to nutrition among overweight women Background: High consumption of food without emotional control or mindless eating has been identified may increase the prevalence of overweight among urban women. Mindful eating intervention has been identified may improve nutritional status among overweight. However, the mechanism of whether this intervention may influence nutritional knowledge and attitude remains unknown. Objective: The study investigates the effectiveness of mindful eating videos on nutritional knowledge and attitude among urban women with overweight. Methods: The research method was used pre-experimental with a one-group pretest-posttest research design on 42 overweight women aged 20-29 years in West Java and Jakarta. The intervention was carried out for 5 weeks using validated mindful eating videos. Knowledge and attitudes were measured by pre-test and post-test questionnaires. Data analysis was carried out by paired sample t-test and Wilcoxon test. Results:  The results of this study indicate that the provision of mindful nutrition education video is not effective in increasing knowledge related to nutrition (p-value= 0.082) while effective in improving attitudes related to nutrition (p-value=0.0001).Conclusions: Nutrition awareness education with online videos can be used as a media for nutritional intervention that affects attitudes related to nutrition, but does not affect the increase in knowledge of women with overweight.